5. Peran BULOG dalam stabilisasi harga beras di pasar domestik Indonesia - Suparmin Suparmin (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2006)
ABSTRAK Tujuan penelitian adalah menganalisis peran Bulog dalam stabilisasi harga beras. Data yang digunakan adalah data sekunder. Data dianalisis dengan menggunakan metode Kointegrasi dan Model Vektor Koreksi Galat. Hasil penelitian menyimpulkan bahwa Bulog hanya berperan dalam stabilisasi harga beras pada rezim Pasar Terbuka Terkendali saja. ABSTRACT The objective of this study is to analyze the role of Bulog in stabilizing rice price. Data were collected from secondary source. Data were analyzed by making use of co-integration, and Vector Error Correction Model (VECM) methods. Results of the study showed that Bulog have a role only in stabilizing the rice price in the Controlled Open Market Regime.